Analisis Pengaruh Kualitas Pelayanan, Kualitas Produk, dan Harga terhadap Kepuasan Pelanggan: Studi Kasus pada Toko Fadistron - Lia Anggraini I.DJ Amahala (CV. Kalimasada Group, 2025)
The purpose of this study is to evaluate the influence of service quality, product quality, and price on the level of consumer satisfaction at Fadistron Stores. The approach used is quantitative through the survey method, with data collection carried out through the distribution of questionnaires to customers who have used products or services from the store. Data analysis was performed using multiple linear regression with the help of SPSS software version 29. The findings of the study revealed that service quality had a significant negative influence on customer satisfaction (coefficient -0.073; significance 0.039). Product quality has a positive but insignificant effect (coefficient 0.068; significance 0.113), while price has a positive and significant effect (coefficient 0.163; significance 0.000). Simultaneously, three independent variables affect customer satisfaction. The VIF and Tolerance values show the absence of multicollinearity, so the regression model is reliable. These findings show that price is the most dominant factor in influencing customer satisfaction, while improving service quality needs further attention.